Students‘ Perspective on Innovative Teaching Model Using Edmodo in Teaching English Phonology: A Virtual Class Development - Nurhayati, Dwi Astuti Wahyu (Dinamika Ilmu, 2019)
This paper displayed the students’ perspective on innovative teaching model using edmodo in teaching English Phonology as a virtual class development. The data were collected for 6 months starting from compiling proposal in March 2018 to August 2018 in the IAIN Tulungagung campus in the sense of data collection, report preparation, group meetings and most other activities carried out in the Tulungagung and Kediri areas. It involves people who have relevant information about the research theme, they are 46 students from the fourth semester in English majors who answered the pre-observation questionnaire, and post questionnaires but 46 interviewees, consisting of thirty-one women and sixteen men, were interviewed. The data was analysed using a descriptive qualitative approach. The finding revealed that the experienced students of using edmodo affected their readiness to take a part in English Phonology teaching using edmodo as a learning medium. The result of this study proved that the experienced students of using edmodo influences the fluency in learning phonology courses so they found it easier to apply Edmodo, serving as on the advantages (time-effective & efficient, not oblivious about computers, simplifying learning material, interactive, communicative, expressive, reducing cheating task, recognizing class management, creating reading habit) and disadvantages of using edmodo, similarly limited lexical items in content courses; differences in the level of competency, motivation, learning environment and background of previous learning; inadequate internet network; prefer to use gadgets for entertainment communication.